The Integration of Small and Medium Business in Eu: Problems and the Way of Resolve - Simanavičienė, Žaneta (Ekonomika, 2003)
This article is about Lithuanian small and medium business and it. integration problems in EU. There arc many problems for small and medium business: a lack of working capital and business information, absence of competitive business idea, large restraint in business regulation and others. The author explains what is necessary for appropriated conditions for small and medium business and for development it .. practical activities. There are many possible ways to solve problems related with coming integration: to create favorable conditions, to differentiate the governmental attitude of different lays of businessmen, to create a competition environment and orientation for social problems of small and medium business. The author represents a business supporting forms, analyses the financial support of business. E..tablishing a clearcut definition of a small and medium business is no casy task. There is no single definition of what a small and medium business is. The Lithuanian government define a small and medium business as medium-sized enterprises, small enterprises (including micro·enterprises) and natural persons who shall, in the manner prescribed by law, enjoy the right to engage in independent commercial, production, professional or similar activities, including the activities which require a business certificate. According to the “Republic of Lithuania law on small and medium-sized business” a medium sized-enterprise is a firm that meets following conditions: less than 250 employees work in such enterprise and the annual income of the enterprise does not exceed LTL 138 million or the book value of the enterprise’s assets does not exceed LTL 93 million. A small enterprise is a firm that meets following conditions: less than 50 employees work in such enterprise and the annual income of the enterprise dues not exceed LTL 24 million or the book value of the enterprise’s assets does not exceed LTL 17 million. A micro-enterprise shall be a small enterprise which complies with all the following conditions: less than 10 employces work in such enterprise and the annual income of the enterprise does not exceed LTL 7 million or the book value of the enterprise’s assets does not exceed LTL 5 million. In Lithuania small businesses exist in every type of trade, manufacturing, construction and services. In order of importance. however, they arc most important in retail trade, services, wholesale manufacturing. Entrepreneurs in small firms have been so successful at meeting the demands of rapidly changing markets that managers in large corporations have tried to mimic their results. Corporate managers’ attempts have focused on creating small, free-wheeling, innovative units within the traditional, often rigid, company hierarchy. Small firms arc typically more flexible than large firms.